Awareness on The Harmful Effects of Fried Food Among Dental Students - M, KAMALLI.; GANAPATHY, DR. DHANRAJ; SASANKA, L. KEERTHI (The journal of contemporary issues in business and government, 2020)
Fried food is a cooking method in which food is submerged in oil. The more we consume these , the less is the intake of essential nutrients and vitamins in the body. Consumption of junk food can lead to a lot of health problems. Fried food can cause dental distress, headache, acne and a lot more. More oil is unhealthy as it elevates the amount of cholesterol in the body. The type of oil used determines the health risks related with fried foods. The aim of the study is to determine the awareness of the harmful eﬀects of fried food among dental students. Self administered questionnaire was designed based on the eﬀects of fried food. The questionnaire was distributed through an online survey planet link. The study population included dental students. The participants were explained about the purpose of study in detail. The questions were carefully studied and corresponding answers were marked by the participants. The data was collected and statistically analysed. 76% of the participants agree that junk food is unhealthy. 94% of the participants felt that fried food makes them fat. 82% of them consume fried food once in a week, 12% consume everyday and 6% consume fried food once in a month. 62% of the participants were willing to give upon fried food considering their health. The study concluded that awareness on the harmful effects of fried food among dental students was satisfactory.